Code-Mixing on Denny Sumargo’s YouTube Channel Selected Podcast - Munthe, Ibrani Herbinson; Rohati, Titi Dewi; Wibowo, Ary Iswanto; Khairunas, Sayyid (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
The research aims to analyze the phenomenon of Bilingualism, Sociolinguistics, and code-mixing, that occurs in daily conversations, providing insight into how bilingual individuals manage language effectively and emphasizing the importance of context in language use. Code-mixing refers to the use of two or more languages in a single sentence or expression. This research uses a descriptive qualitative method by repeatedly watching Denny Summargo’s Podcast with Maudy Ayunda in an episode entitled “Sombong & Star Syndrome!? Aku Hampir Batal nikah dengan Jesse Choi!! Maudy Ayunda-Curhat Bang” and referring to theories from books and journals as data collection techniques. The researcher concluded the results of his findings where the out of 135 data, 107 data used the Intra-Sentential Mixing type, 22 data used Intra-Lexical Mixing, 5 data used Clause Level Mixing and 1 data used Tag Mixing. The findings reveal type of code- mixing. Factors such as habits, environmental influences, repetition, the intention to clarify speech content, and the expression of group identity were identified. Abstrak Penelitian ini bertujuan untuk menganalisis fenomena bilingualisme, sosiolinguistik, dan campur kode yang terjadi dalam percakapan sehari-hari, memberikan wawasan tentang bagaimana individu bilingual mengelola bahasa secara efektif dan menekankan pentingnya konteks dalam penggunaan bahasa. Campur kode mengacu pada penggunaan dua bahasa atau lebih dalam satu kalimat atau ekspresi. Penelitian ini menggunakan metode kualitatif deskriptif dengan menonton berulang kali podcast youtube channel Denny Sumargo Bersama Maudy Ayunda dalam satu episode berjudul “Sombong & Star Syndrome!? Aku Hampir Batal nikah dengan Jesse Choi!! Maudy Ayunda-Curhat Bang” dan merujuk pada teori dari buku dan jurnal sebagai teknik pengumpulan data. Peneliti menyimpukan hasil dari temuannya dimana dari 135 data terdapat 107 data yang menggunakan tipe Intra-Sentensial Mixing, 22 data menggunakan Intra-Lexical Mixing, 5 data menggunakan Clause Level Mixing dan 1 data menggunakan Tag Mixing. Temuan penelitian mengungkap jenis campur kode. Faktor-faktor seperti kebiasaan, pengaruh lingkungan, pengulangan, niat untuk memperjelas isi tuturan, dan ekspresi identitas kelompok diidentifikasi.